2016
DOI: 10.1515/quageo-2016-0001
|View full text |Cite
|
Sign up to set email alerts
|

Geodiversity and Biodiversity of the Postglacial Landscape (Dębnica River Catchment, Poland)

Abstract: NAJWER A., BORYSIAK J., GUDOWICZ J., MAZUREK M., ZWOLIŃSKI ZB., 2016. Geodiversity and biodiversity of the postglacial landscape (dębnica river catchment, Poland). Quaestiones Geographicae 35(1), Bogucki Wydawnictwo Naukowe, Poznań, pp. 5-28, 12 fi gs, 4 tables. ABSTRACT:The preparation of a proper zoning plan or landscape-ecological plan requires taking into account recognition of the natural values of an area covered by the plan and evaluating its abiotic and biotic diversities. The aim of the paper is to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 22 publications
0
33
0
1
Order By: Relevance
“…4) has three distinct phases: pre-processing, analysis and deliverables (results). The workflow generally follows the procedures proposed by Pellitero et al (2015) and Najwer et al (2016), while keeping in mind the purpose and scope of this study. Important steps were the acquisition and selection of freely available data from existing databases, the development of environment-specific geodiversity assessment indices, the computation of Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…4) has three distinct phases: pre-processing, analysis and deliverables (results). The workflow generally follows the procedures proposed by Pellitero et al (2015) and Najwer et al (2016), while keeping in mind the purpose and scope of this study. Important steps were the acquisition and selection of freely available data from existing databases, the development of environment-specific geodiversity assessment indices, the computation of Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Broadly, geodiversity and its quantification have their roots in geoconservation and scientific applications (Gray 2013, Zwoliński et al 2017, with a focus on geoheritage and geotourism (Zwoliński and Stachowiak 2012, Knight et al 2015, Newsome andDowling 2017), nature conservation (Burek andProsser 2008, Pellitero et al 2011), and land management (Pereira et al 2013, Seijmonsbergen et al 2014, Pellitero et al 2015, Silva et al 2015, Najwer et al 2016, Araujo and Pereira 2017. More recently, (com-ponents of) geodiversity have been used to explain the distribution of biodiversity resulting from landscape patterns (Hjort et al 2015, Bailey et al 2017.…”
Section: Introductionmentioning
confidence: 99%
“…We must not forget that geodiversity is the basis for biodiversity, and together they constitute the diversity of landscape structure on the Earth's surface, including the area of the planned geopark. The geodiversity and biodiversity of the postglacial landscape in nearby Dębnica river catchment (which partially covers the area of the current research) were presented lately by Najwer et al (2016).…”
Section: Study Areamentioning
confidence: 99%
“…Geodiversity has been proposed as a useful approach to explore and understand biodiversity patterns (Jačková & Romportl, 2008;Jedicke, 2001;Najwer, Borysiak, Gudowicz, Mazurek, & Zwoliński, 2016;Parks & Mulligan, 2010). In recent years, Conserving Nature's Stage (CNS) has been advanced as an important conservation principle stating that geodiversity could be used as a coarse filter strategy for conserving biodiversity (Beier, Hunter, & Anderson, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Still, the relationships between explicit geodiversity and biodiversity measures have been examined rarely. Recent studies have explored the links between geodiversity and biodiversity in landscape scale (Bailey, Boyd, & Field, 2018;Hjort et al, 2012;Jačková & Romportl, 2008;Kougioumoutzis & Tiniakou, 2014;Najwer et al, 2016;Tukiainen et al, 2017). These studies have shown that geodiversity may help explain spatial biodiversity patterns at mesoscale levels.…”
Section: Introductionmentioning
confidence: 99%